Sponsorship and patronage and beyond: PPP as an innovative practice in the management of cultural heritage. Issue 2 (15th May 2017) - Settembre Blundo, Davide; García Muiña, Fernando Enrique; Fernández del Hoyo, Alfonso Pedro; Riccardi, Maria Pia; Maramotti Politi, Anna Lucia
Abstract : Purpose: The purpose of this paper is to present alternative management practice methods for the cultural heritage sector apart from the traditional public support model. These alternatives rely on sponsorship and patronage as well as the newer and more innovative public-private partnership (PPP). Design/methodology/approach: The paper is organized in two conceptual sections based on a literature review. The first section presents and compares two closely associated business strategy forms that are increasingly becoming popular within companies: sponsorship and patronage. These strategies are analyzed to show their advantages and disadvantages and are assessed based on their best uses in terms of the benefits from their implementation to all stakeholders involved (benefactors, recipients and the public) and, more particularly, to the benefactor's company communication policy. The second section analyzes the PPP as a newer innovative practice in the cultural heritage sector, a recent development that has great potential, especially during an economic crisis where public funds are reduced, which risks the future recovery and proper maintenance of sites. Findings: In the paper, the authors stressed that sponsorship, patronage and PPP are not merely alternative ways of primarily obtaining government funding for the cultural heritage sector but are also new strategic management practices that, when properly performed, will not only preserve and improve the sector but also allow more value to be distributed among all stakeholders. Originality/value: Although the topic of PPP is treated fairly in the scientific literature, especially with regard to infrastructure, there are few cases of the application of this model to cultural heritage management.